Prognostic Value of Semiautomatic CT Volumetry in Patients With Stage I Non–Small Cell Lung Cancer Treated With Stereotactic Body Radiation Therapy. Issue 3 (May 2016) - Satoh, Yoko; Motosugi, Utaroh; Nambu, Atsushi; Saito, Akitoshi; Onishi, Hiroshi
Abstract : Objective: The aim of this study was to examine the prognostic value of semiautomated 3-dimensional image analysis-based parameters from pretreatment computed tomography (CT) in patients with non–small cell lung cancer treated with stereotactic body radiation therapy. Methods: We evaluated 91 patients. We defined 2 parameters: (1) VOL, extracted tumor volume with a threshold ≥ −400 HU; and (2) ATN, the mean CT attenuation value. The maximum standardized uptake value (SUVmax ) was recorded as 18 F-fluorodeoxyglucose positron emission tomography/CT parameter. The prognostic values were assessed using the Kaplan-Meier and a Cox proportional hazards analysis. Results: Overall survival and progression-free survival were significantly worse in patients with larger VOL, higher ATN, and higher SUVmax . VOL was an independent indicator of overall survival, whereas ATN was an indicator of progression-free survival, lymph node recurrence, and distant metastasis. However, SUVmax was not an independent prognostic factor for either outcome. Conclusions: VOL and ATN from 3-dimensional image analysis of CT scans have prognostic values for non–small cell lung cancer patients treated with stereotactic body radiation therapy.